Pembuatan pupuk organik padat dari sisa sayuran dan buah di Green House Universitas Sulawesi Barat sebagai sarana pemberian ilmu bagi mahasiswa: Production of solid organic fertilizer from vegetable and fruit waste in the West Sulawesi University Greenhouse as an educational medium for students - Akbar Akbar; Aldiansah Aldiansah; Jaris Akmal Kuncoro; Dasmin Dasmin; Hasrat Aswad; Renol Renol; Frengky Frengky; Dwi Yulianti Amir; Sahamia Sahamia; Zulaikha Zulaikha; Mutmainna Mutmainna; Febriyanti Febriyanti; Rosmini Rosmini; Rini Fitriani; Damayanti Damayanti (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2026)
Inorganic or chemical fertilizers are often used by farmers to increase crop yield and quality in a short period of time. However, continuous use of inorganic fertilizers in high doses can reduce soil fertility, disrupt the balance of microorganisms, and pollute the environment. To address these impacts, the use of organic fertilizers becomes an environmentally friendly alternative that can improve soil structure and sustainably increase agricultural productivity. This practical experiment aims to understand the process of making vermicompost from a mixture of household organic waste and animal manure, as well as to evaluate the quality of the resulting vermicompost. The methods used include preparation of raw materials, pre-composting for seven days, worm inoculation, and maintenance of the medium for 30 days. The results of the experiment show that the vermicomposting process can accelerate the decomposition of organic materials and produce organic fertilizer with a fine texture and brown color. dark brown, with an earthy smell. Nutrient content analysis showed an increase in nitrogen and phosphorus levels compared to the raw material. Thus, the resulting vermicompost is suitable for use as an organic fertilizer for an increase in nitrogen and phosphorus levels compared to the initial material. Thus, the resulting vermicompost is suitable for use as an organic fertilizer to improve soil fertility and support sustainable agricultural cultivation.